Schedule Risk Analysis of EPC Project for Power Transmission and Transformation Project Led by Design Enterprise. (September 2020) - Zhao, Zhongze; Meng, Qichen; Pang, Nansheng
Abstract: The advantage of the EPC model is that it can alleviate the contradictions of all parties, integrate resources, and release the owners from management pressure. However, the various risks in the whole life cycle of the power transmission and transformation project are complicated, and the schedule management is the weak point of the EPC general contractor with the design as the leader, and the management of the project schedule is directly related to the profit and reputation of the general contractor. Therefore, this paper will comprehensively analyze the potential schedule risk in combination with the characteristics of power transmission and transformation engineering, and use the set pair analysis principle to establish a fault tree risk analysis model to evaluate the schedule risk of the EPC project of the power transmission and transformation project led by the design enterprise.